Downregulation of METTL7B Inhibits Proliferation of Human Clear Cell Renal Cancer Cells In Vivo and In Vitro - Li, Wei; Xu, Shi; Peng, Naixiong; Zhang, Zejian; He, Hua; Chen, Ruoyu; Chen, Dong; Fan, Jiqing; Wang, Xisheng (Frontiers in Oncology, 2021)
Clear cell renal cell carcinoma (ccRCC) is the most aggressive urologic tumor, and its incidence is increasing. Identifying novel molecular biomarker for inhibiting the progression of ccRCC will facilitate developing new treatment strategies. Although methyltransferase-like 7B(METTL7B) was identified as a Golgi-associated methyltransferase, the function and mechanism of METTL7B in ccRCC development and progression has not been explored. METTL7B expression were significantly up-regulated in ccRCC tissues(n=60), which significantly associated with TNM classification, tumor size, lymph node metastasis and poor prognosis for ccRCC patients. Functional studies showed that down-regulation of METTL7B inhibited cell proliferation, migration in vitro and xenograft tumor formation in vivo. In addition, METTL7B knockdown promoted cell cycle arrest at G0/G1phase and induced cellular apoptosis. Taken together, down-regulation of METTL7B inhibits ccRCC cell proliferation and tumorigenesis in vivo and in vitro. These findings provide a rationale for using METTL7B as a potential therapeutic target in ccRCC patients.